Boundedness of fractional differential operator in complex spaces - W. Ibrahim, Rabha; Kilicman, Adem; Esa Abdulnaby, Zainab (World Scientific Publishing, 2017)
In this work, we introduce some properties of a complex fractional differential operator. The boundedness and some other properties are studied in view of geometric function theory.